THE CORRELATION BETWEEN THE ROLE OF NURSES AS EDUCATORS AND MEDICATION ADHERENCE IN DIABETES MELLITUS PATIENTS AT RAWALUMBU BEKASI HOSPITAL IN 2023 - Sitopu, Lusiana Hotmaria; Simamora, Rotua Suriany; Ani Anggraini (Jurnal Medicare, 2024)
Diabetes Mellitus (DM) known in Indonesia  as "Diabetes"  is a disease whose prevalence is now increasing. The role of the educator itself is to help patients to improve their health by providing health education and medical actions received so that clients or families can know knowledge that is important to patients or families. This study aims  to analyze the relationship between the role of nurses as educators with adherence to Treatment P there is Pasien DM at Rawalumbu Bekasi Hospital in 2023. The research method used is quantitative analytical observational with Cross Sectional Study approach and total sampling technique, which is to select samples based on the frequency distribution of patient respondent characteristics. The samples used in this study were 60 diabetes mellitus patients who were treated in the inpatient room at Rawalumbu Bekasi Hospital. The results of the study identified the role of nurses as good educators with medication adherence in non-adherent diabetes mellitus patients totaling 25 respondents (41.7%). There are Chi-Square  test results with a significant level of 95% or a value of α 5% (0.05) obtained p value (0.000) < a value of α (0.05)  so that it can be concluded from the results Ho rejected means that there is a relationship between the role of nurses as educators with treatment compliance in diabetes mellitus patients at Rawalumbu Bekasi Hospital in 2023.